2008
DOI: 10.1111/j.1365-2567.2007.02746.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential contribution of TAP and tapasin to HLA class I antigen expression

Abstract: Summary Expression of class I human leucocyte antigens (HLA) on the surface of malignant cells is critical for their recognition and destruction by cytotoxic T lymphocytes. Surface expression requires assembly and folding of HLA class I molecules in the endoplasmic reticulum with the assistance of proteins such as Transporter associated with Antigen Processing (TAP) and tapasin. Interferon‐γ induces both TAP and tapasin so dissection of which protein contributes more to HLA class I expression has not been poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 61 publications
(76 reference statements)
4
31
1
Order By: Relevance
“…This result is different from those of previous studies that established the TAP-stabilizing function of tapasin using other cell line systems (12,(45)(46)(47). Several possibilities may explain this discrepancy.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This result is different from those of previous studies that established the TAP-stabilizing function of tapasin using other cell line systems (12,(45)(46)(47). Several possibilities may explain this discrepancy.…”
Section: Discussioncontrasting
confidence: 99%
“…Later, Yabe et al (35) described a large homozygous deletion of exons 4 -7 in TAPBP in PBMC obtained from a patient with type II bare lymphocyte syndrome. More recently, Belicha-Villanueva et al (12) revealed a tapasin-loss phenotype by the M553 melanoma cell line, although its underlying mechanism remains unclear. We report here the first case of tapasin loss caused by a combination of genetic defects (TAPBP 684delA and LOH) in a malignant cell, although TAPBP 684delA appears to be cancer-unrelated as it is present as a heterozygous germ-line mutation that becomes homozygous after cancer-related LOH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cif Inhibits TAP-mediated Peptide Transport into the ER and Cell Surface MHC Class I Antigen Presentation-To determine whether Cif, by decreasing TAP1 abundance, reduced TAPmediated transport of peptides into the ER, studies were conducted to measure peptide translocation into the ER by measuring 125 I-labeled peptide translocation into ER microsomes of airway epithelial cells, as described (11). (ϩCif) OMVs reduced peptide uptake by 61 Ϯ 7%, compared with peptide uptake in cells treated with (ϪCif) OMVs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Peptide Translocation Assays-Peptide translocation was measured as described previously using 125 I-labeled B27#3 glycopeptide-1 and ER microsomes prepared from (ϩCif) OMVor (ϪCif) OMV-treated polarized airway epithelial cells (11).…”
Section: Methodsmentioning
confidence: 99%